Non-familial cherubism: A case report with its surgical management - Shital A Hungund; Vatsala Singh; Chaitra Nagaraja (Wolters Kluwer Medknow Publications, 2013)
Cherubism is an autosomal-dominant inherited syndrome; it starts in early childhood and involutes by puberty. It is characterized by excessive bone degradation of the jaws and development of fibrous tissue masses. Non-familial cherubism is a rare entity, which needs to be documented. This paper describes the findings of non-familial cherubism. An 11-year-old male patient reported with bilateral swellings of the jaws and unerupted teeth. Extensive gingival overgrowth, cherubic facial appearance, multilocular osteolytic lesions in radiographs and family history lead to the diagnosis of non-familial cherubism. Treatment included full mouth excision of the gingival tissue by gingivectomy with both manual instrumentation and electrosurgery. Patient is being monitored and recalled for frequent follow-ups. Dental practitioners need to be alert with patients presenting with gingival overgrowth.